Understanding the conceptualisation and strategies of service recovery processes in service organisations. (23rd May 2023) - Anwar, Sohail
Many service providers struggle with service recovery (SR) processes, since they do not directly involve customers, and have no bearing on the needs and expectations of customers. The way in which compensation and complaint resolutions are delivered can have a significant impact on how customers perceive of SR and retention efforts in organisations. This study unpacks conceptualisations and the practicality of SR processes in service providing organisations. To meet these objectives, data were collected from reputed public banks using online reviews, semi-structured interviews, and focus group discussion. The results reveal that disruption and frustration typically occur during the first stage of service failure, and there is therefore a need to redesign SR processes so that employees can identify the causes of disruption and understand what customers expect from service providers. This study highlights that focussed engagement, help, feedback, improvements, complaint handling, fair compensation, fast services, apologies, customer participation, the credibility of feedback, and competence are some important factors that can improve the SR processes of public banking organisations. This study presents a conceptual framework that illustrates how SR processes can help banking organisations improve the usefulness of SR processes.